Peran Kepuasan Kerja Dalam Memediasi Hubungan Antara Peran Kepemimpinan Dan Kompensasi Terhadap Kinerja Pegawai - Yuhan Sahri; Evi Susanti Tasri (CV. ITTC INDONESIA, 2022)
The UPTD of the Protected Forest Management Unit (KPHL) of Pasaman Raya is one of the regional technical implementing units of the Forestry Service of West Sumatra Province. So it becomes interesting to examine the performance of these employees. This study aims to analyze the performance that is influenced by the variables of leadership and compensation and the mediating role of job satisfaction. The results of this study state that partially there is a significant influence between leadership and positive and insignificant effect on performance, leadership has a positive and insignificant effect on job satisfaction, compensation has a significant positive effect on employee performance, compensation has a positive and significant effect on job satisfaction, goals work has a positive and significant effect on performance, work goals become an intervention between leadership and performance and have an insignificant effect and work disruption between compensation and performance has a significant effect.